Keanekaragaman jenis dan perilaku menggigit vektor malaria (Anopheles spp.) di Desa Lifuleo, Kecamatan Kupang Barat, Kabupaten Kupang, Nusa Tenggara Timur - Rahmawati, Ety; Hadi, Upik Kesumawati; Soviana, Susi (Jurnal Entomologi Indonesia, 2014)
Malaria is a preventable and treatable mosquito-borne diseases, whose main victims are children and pregnant women. Indonesia is the second most affected region in South East Asia and has the the highest malaria burden after India. The research was aimed to study the species diversity and biting activity of malaria vectors (Anopheles spp.) in Lifuleo Village, West Kupang District, Kupang Regency, East Nusa Tenggara Province. The mosquitoes was collected by using (1) the human landing collection technique, (2) aspirators for collecting mosquitoes resting on the wall of houses and cow barn, and (3) light traps. The research was done for four months. The result showed that there were six species of Anopheles i.e., An. barbirostris, An. subpictus, An. annularis, An. vagus, An. umbrosus and An. indefinitus. An. barbirostris and An. subpictus were two species with the highest density. The value of man hour density (MHD) indoor and outdoor for An. barbirostris were 5.45 and 6.23 respectively, and for An. subpictus were 1.35 and 1.56, respectively. The blood sucking activity indoor and outdoor for An. barbirostris occured at 22:00 to 4:00 and 21:00 - 04 respectively, whereas for An. subpictus at 8:00 p.m. to 21:00 and 22:00 to 23:00, respectively. Based on the value of man hour density the mosquito Anopheles spp. in Lifuleo village were exophagic and exophilic.